DNA-Based Storage: Trends and Methods - Hossein Tabatabaei Yazdi, S. M.; Han Mao Kiah; Garcia-Ruiz, Eva; Jian Ma; Huimin Zhao; Milenkovic, Olgica (IEEE transactions on molecular, biological, and multi-scale communications, 2015)
We provide an overview of current approaches to DNA-based storage system design and of accompanying synthesis, sequencing and editing methods. We also introduce and analyze a suite of new constrained coding schemes for both archival and random access DNA storage channels. The analytic contribution of our work is the construction and design of sequences over discrete alphabets that avoid pre-specified address patterns, have balanced base content, and exhibit other relevant substring constraints. These schemes adapt the stored signals to the DNA medium and thereby reduce the inherent error-rate of the system.